Purification, crystallization and crystallographic analysis of Clostridium thermocellum endo-1,4-β-D-xylanase 10B in complex with xylohexaose - Najmudin, Shabir (2019)
The cellulosome of Clostridium thermocellum is a highly organized multi-enzyme complex of cellulases and hemicellulases involved in the hydrolysis of plant cell-wall polysaccharides. The bifunctional multi-modular xylanase Xyn10B is one of the hemicellulase components of the C. thermocellum cellulosome. The enzyme contains an internal glycoside hydrolase family 10 catalytic domain (GH10) and a C-terminal family 1 carbohydrate esterase domain (CE1). The N-terminal moiety of Xyn10B (residues 32-551), comprising a carbohydrate-binding module (CBM22-1) and the GH10 E337A mutant, was crystallized in complex with xylohexaose. The crystals belong to the trigonal space group P3221 and contain a dimer in the asymmetric unit. The crystals diffracted to beyond 2.0 Å resolution.